Rebalancing China's economy : what does growth theory tell us? - Aziz, Jahangir (IMF working paper ;, 2006)
This paper uses the standard one-sector neoclassical growth model to investigate why China's consumption has been low and investment high. It finds that the low cost of capital has been quantitatively an important factor. Theory predicts that the price of capital may have been significantly distorted in the 1990s and 2000s. The distortion could have been caused by nonperforming loans, borrowing constraints, and uncertainty over changes in government guidance in bank lending. If China is to rebalance growth towards relying more on consumption and less on exports and investment, banking sector reforms and financial market development could, therefore, turn out to be key.